2015
DOI: 10.1007/s10310-014-0474-x
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic water use efficiency in wet and dry years at young and old plantations of Pinus sylvestris var. mongolica in semiarid China

Abstract: Rainfall is the most important factor influencing the growth and survival of Mongolian pine (Pinus sylvestris var. mongolica), but the responses of these trees to extremes of rainfall are still poorly understood. Intrinsic water use efficiency (iWUE, as proxied by d 13 C), specific leaf area, dry matter content, soil water content and groundwater level were measured in 18-year-old and 38-year-old Mongolian pine stands (young and old) during two conservative years with extreme rainfalls (280 mm, 2009; and 580 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 33 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…Our previous results suggested that the δ 13 C values of three plant species show varying degrees of negative correlation with the comprehensive soil conditions and soil water contents, but they are also related to temperature and precipitation. Moreover, other researches demonstrated a tighter link between δ 13 C value and soil depth than with climate conditions in Pinus sylvestris, because of the amount of water available to roots [38,39]. This inferred that under well-watered and mild temperature conditions, where soil water retention capacity is low, soil properties related to an enhance water retention should be the key factor conditioning carbon isotopic composition on plant tissues.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Our previous results suggested that the δ 13 C values of three plant species show varying degrees of negative correlation with the comprehensive soil conditions and soil water contents, but they are also related to temperature and precipitation. Moreover, other researches demonstrated a tighter link between δ 13 C value and soil depth than with climate conditions in Pinus sylvestris, because of the amount of water available to roots [38,39]. This inferred that under well-watered and mild temperature conditions, where soil water retention capacity is low, soil properties related to an enhance water retention should be the key factor conditioning carbon isotopic composition on plant tissues.…”
Section: Discussionmentioning
confidence: 95%
“…Common tree species growing at different soil depths (or under different nutrient conditions) in rocky desertification areas normally exhibit two types of responses with regard to the δ 13 C value. First, the δ 13 C value has been shown to change non-significantly for species such as Acer buergerianum and Mallotus repandus; second, the δ 13 C value decreases with increasing soil depth for species such as Mallotus philippinensis and Pistacia weinmannifolia; the latter response is the dominant mode [38]. In deep soils with poor nutrient conditions, the δ 13 C values of plants in karst mountainous areas have shown both positive and negative responses [19].…”
Section: Discussionmentioning
confidence: 99%
“…Significantly higher needles δ 13 C in the dry period than in the wet period for the Mongolian pine trees growing at both the bottom and top of sand dunes indicated that the Mongolian pine trees could adjust the WUE under drought condition. In general, the WUE can be inferred by using the δ 13 C of plant tissues based on the simpler linear model of Farquhar et al [57], which makes the assumption that mesophyll conductance to CO 2 is infinite, whereby a higher WUE is indicated by a higher δ 13 C [36,58]. The leaf δ 13 C typically increases with decreasing water availability, as a result of the stomatal closure and reduced transpiration and prevents their hydraulic system from irreversible damage [59].…”
Section: Water Uptake and Water Use Efficiency Of Trees During The Drmentioning
confidence: 99%
“…Nitrogen and water are considered to be important limiting factors for plant growth performances in the southeast of Horqin Sandy Land [35,36]. A good possibility for enhancing nutrients and soil water availability in the region could utilize the SS originating from wastewater treatment plants.…”
Section: Introductionmentioning
confidence: 99%